In Vitro Antileishmanial Activity of Resveratrol Originates from its Cytotoxic Potential against Host Cells - Lucas, Ina Katharina; Kolodziej, Herbert (Planta Medica, 2013)
In addition to a range of beneficial pharmacological activities, resveratrol is recently reported to have potential antileishmanial activities in vitro. The present study was conducted to evaluate the effect of resveratrol on promastigotes and amastigotes of transgenic Leishmania major expressing green fluorescent protein in comparison with its direct cytotoxic effects on host cells (bone marrow-derived and J774-G8 macrophages, respectively). As assessed by FACS analysis, resveratrol showed moderate antipromastigote activity at < 35 µg/mL (153.2 µM) and promising effects at higher sample concentrations. In contrast, the green fluorescent protein signal as a measure of the intracellular parasitesʼ viability was reduced in a concentration-dependent manner. Resveratrol strongly inhibited NO production, but did not display direct NO-scavenging activity in sodium nitroprusside solution. Western blotting indicated that resveratrol reduced recombinant interferon-γ/LPS-induced expression of iNOS protein. Microscopic studies, MTT evaluation, and FACS analysis showed significant cytotoxic effects on host cells in a concentration-dependent manner. This finding suggests that the in vitro antileishmanial activity of resveratrol is due to cytotoxic effects on host cells rather than attributable to a specific antiparasitic potential.
Keywords: Leishmania major GFP; resveratrol; macrophages; antileishmanial activity; nitric oxide; cytotoxicity